Enhanced activity and selectivity in n-octane isomerization using a bifunctional SCILL catalyst - Meyer, Carolin; Hager, Veit; Schwieger, Wilhelm; Wasserscheid, Peter (Journal of Catalysis, 2012)
Bifunctional Solid Catalyst with Ionic Liquid Layer (SCILL) systems are presented and applied in the skeleton isomerization of n-octane in a slurry-phase reaction mode. It is demonstrated that Pt on silica, coated with a thin film of acidic chloroaluminate ionic liquid exhibits remarkable catalytic performance under mild conditions in the presence of hydrogen. Interestingly, both selectivity and activity of n-octane isomerization increase in these systems as a function of hydrogen pressure. This does not only suggest a hydrogenation activity of the catalytic Pt-centers embedded in the strongly Lewis acidic ionic liquid but also a significant increase in the proton acidity in this system as a function of the hydrogen pressure.